Patofiziološki mehanizmi pri odtegnitvenem sindromu novorojenčka - Nanić, Lejla (Medicinski razgledi, 2022)
Neonatal abstinence syndrome is a set of signs that appear after birth, when after prolonged passive exposure of the fetus to psychotropic substances consumed by the mother during pregnancy, the exposure suddenly ceases. Signs of withdrawal in the newborn usually appear two to three days after birth due to increased activation of the central and autonomic nervous system. They occur due to the increased production and release of norepinephrine, acetylcholine, corticotropin and other substances, and the reduced production and secretion of dopamine and serotonin. The most common signs of withdrawal are tremor, irritability, excessive crying, feeding difficulties, sleep disturbances, increased muscle tone, fever, sweating, tachypnea, tachycardia, vomiting, and diarrhea, but may also include convulsions. The pathophysiological withdrawal mechanisms from different groups of psychotropic substances (opioids, stimulants, antidepressants, anxiolytics, alcohol, cannabis) differ. Neonatal withdrawal syndrome is clinically expressed differently and cannot be fully explained. In addition to the degree of exposure of the fetus to psycho - tropic substances and their pharmacological properties, the expression of signs is also influenced by gestational age and the newborn’s associated diseases. Much of the variability in the clinical course is due to genetic and epigenetic factors, which are not yet routinely determined in clinical practice.
Keywords: novorojenčki; odtegnitveni sindrom; patofiziologija